PENGARUH HARGA, FASILITAS, DAN PROMOSI TERHADAP KEPUTUSAN MENGINAP PADA HOTEL SYARIAH RAUDA KOTA PEKANBARU - Fahriza, Fahriza; Gatot, Wijayanto; Agnes, Alvionita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to determine the influence of price, facilities and promotions on the decision to stay at the Rauda sharia hotel, Pekanbaru city. A business operating in the accommodation sector in the city of Pekanbaru. The population in this study is unknown while the sample is 100 people using a purposive sampling method using the Lames How formula. By using Validity and Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Descriptive Analysis, Multiple Linear Regression Analysis, Partial Hypothesis Test (t Test), Simultaneous Hypothesis Test (f Test) and Coefficient of Determination Test (R²). The type of data used is quantitative data. Meanwhile, the data used is primary and secondary data. Data collection techniques use questionnaires, interviews, documentation and literature study. Based on the reliability test, it shows that all variables have a Cronbach's Alpha value > 0.6. The normality test results show that all data is normally distributed. Based on the multicollinearity test, the tolerance value is > (0.10) and the vif value is < (10). Based on the Heteroscedasticity Test, it shows that heteroscedasticity does not occur. The results of partial hypothesis testing (t test) show that: price has a significant positive effect on the decision to stay, facilities have a significant positive effect on the decision to stay, promotion has a significant positive effect on the decision to stay. Based on simultaneous hypothesis testing (f test), it shows that price, facilities and promotions have a significant effect on the decision to stay at Rauda sharia hotel consumers in the city of Pekanbaru. Keywords: Price, Facilities, Promotion, Decision to Stay, Sharia Hotel